Key Role of STAT4 Deficiency in the Hematopoietic Compartment in Insulin Resistance and Adipose Tissue Inflammation. (16th March 2017) - Dobrian, Anca D.; Ma, Kaiwen; Glenn, Lindsey M.; Hatcher, Margaret A.; Haynes, Bronson A.; Lehrer, Eric J.; Kaplan, Mark H.; Nadler, Jerry L.
Abstract : Visceral adipose tissue (AT) inflammation is linked to the complications of obesity, including insulin resistance (IR) and type 2 diabetes. Recent data from our lab showed that germline deficiency in STAT4 reduces inflammation and improves IR in obese mice. The objective of this study was to determine the contribution of selective STAT4 deficiency in subsets of hematopoietic cells to IR and AT inflammation. To determine the contribution of hematopoietic lineage, we sublethally irradiated Stat4 −/− C57Bl6 mice and reconstituted them with bone marrow cells (BMC) from Stat4 +/+ C57Bl6 congenic donors. We also established the contribution of selective STAT4 deficiency in CD4+ or CD8+ T cells using adoptive transfer in Rag1−/− mice. All mice received a HFD for 15 weeks (n = 7 –12 mice/group). BMC that expressed STAT4 induced increases in glucose intolerance and IR compared to STAT4-deficient cells. Also, AT inflammation was increased and the numbers of CD8+ cells infiltrating AT were higher in mice with STAT4 expressing BMC. Studies in Rag1−/− mice further confirmed the prominent role of CD8+ cells expressing STAT4 in insulin resistance and AT and islet inflammation. Collectively our results show specific and dominant contribution of STAT4 in the hematopoietic compartment to metabolic health and inflammation in diet-induced obesity.